CONVENTIONALITY CONTROL IN THE ARTAVIA MURILLO CASE AND ITS REFLECTION ON THE FORMATION OF PRECEDENTS IN BRAZIL - ANALYSIS OF ADPF 54 - Camurça Correia, Daniel; Lima, Martonio Mont’Alverne Barreto; Correia, Michele Teles Alencar (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2023)
This article aims to present reflections on the importance of conventionality control in the case of Artavia Murillo et al vs. Costa Rica, which involved the clash between the protection of the life of the embryo on the one hand, and on the other, reproductive rights, the right to private and family life, in addition to the right to autonomy. In this case, the decision formed a precedent, which had as its axis the interpretation of Article 4.1 of the American Convention, a legal device that was later dealt with in Brazil, in the ADPF 54 judgment. Judiciary has been interpreting the protection of life, at the international level, and at the national level. The general objective of this study is to analyze the effect that the precedent formed after the Artavia Murillo case, in Costa Rica, had on the judgment of ADPF 54, in Brazil. The specific objectives are: to understand the role of conventionality control, to analyze the protection of human rights in the Artavia Murillo case and to evaluate the similarity between CORTEIDH's interpretation in the Artavia case and the judgment of ADPF 54. It is defined as problematic: how Did CORTEIDH's decision in the Artavia Murillo case influence the formation of a precedent in Brazil, resulting from ADPF 54? The study points to a criticism of legislative omission. For this purpose, the case study method was used, more precisely the ADPF 54, with a qualitative and analytical approach, reading the bibliography of scholars on conventionality control and international law, such as Ana Maria Lopes and Valério Mazzuoli.Keywords: Conventionality Control. Fundamental rights. Human rights. Inter-American Court of Human Rights. American Convention